Knowing with New Media A Multimodal Approach for Learning - Redman, Lena (Springer Singapore, 2018)
This cutting edge book considers how advances in technologies and new media have transformed our perception of education, and focuses on the impact of the privatisation of digital tools as a mean of knowledge production. Arguing that education needs to adapt to the modern learner, the book's unique approach is based on a disassociation with the deeply ingrained attitude with which people have traditionally viewed education - learning the existing symbolic systems of certain disciplines and then expressing themselves strictly within the operational modes of these systems. The ways of knowledge production - exploring, recording, representing, making meaning of and sharing human experiences - have been fundamentally transformed through the infusion of digital technologies into all aspects of human activity, allowing learners to engage with their immediate natural, social and cultural environments by capitalising on their individual abilities and interests. This book proposes a new approach to teaching and learning termed 'cinematic bricolage', which involves generating knowledge from heterogeneous resources in a 'do-it-yourself' manner while making meaning through multimodal representations. It shows how cinematic bricolage reconnects ways of knowing with ways of being, empowering the individual with a sense of personal identity and responsibility, helping to shape more aware social citizens.